Industrial community energy systems: Simulating the role of financial incentives and societal attributes - Eslamizadeh, Sina; Ghorbani, Amineh; Costa, Rafael Castelo Branco Ferreira; Künneke, Rolf; Weijnen, Margot (Frontiers in Environmental Science, 2022)
Considering that the industrial sector consumes almost one-third of the energy demand globally, it is an urgent call to reduce the carbon footprints in this sector. Among different approaches to meet this goal, such as the employment of carbon capture technologies and increasing energy efficiency within industries, transitioning to renewable electricity (RE) would be another outlook to reduce the carbon footprints and increase the energy security of the industries. Collective power generation within communities has shown to be feasible and promising in the Industrial sector, where groups of industries collaborate to generate energy and meet their energy demand. Given that the literature has so far paid marginal attention to the challenges of establishing the industrial community energy systems (InCES), in this research, we investigated how the initiation and continuation of such systems among industrial companies can take place and what financial incentives can act as the proper supporting systems to be introduced by governments. We used agent-based modelling and simulation, in combination with cost-benefit analysis to assess the feasibility of initiating/joining an InCES by industries. Also, we considered cultural factors in the decision making process of industrial companies. For the cultural context six countries, namely, Japan, Iran, the Netherlands, Australia, Brazil, and the United States, were studied to better generalise this research's findings. The results show that the type of financial incentive schemes does not substantially impact the number of established InCESs, and the number of companies joining/exiting InCES. At the same time, the amount of generated RE is significantly influenced by the type of incentive mechanisms. The Feed-in-Tariff incentive showed the worst performance and the TAX incentive was the best stimuli for the RE generation. Interestingly, the Tradable Green Certificate (TGC) incentive showed almost similar performance to TAX incentive, while its market-dependent nature results in the employment of the most efficient RE technologies by industries.